Acclimatization in the Andes - Historical Confirmations on "climate Aggression" in the development of societies of America - Monge M., Carlos (1945)
Reversible actions and reactions between organism and environment in regard to life upon the American high plateaus lead to en adaptative process whose goal is acclimatization. As a consequence of the alluded interactions the organism may become adjusted either to live in the altitude individual acclimatization or to Iive and to reproduce, race acclimatization. To the author this phase of adjustment (adaptation) implies a form of Mountain Sickness to which he was the first to call attention in 1928. When Mountain Sickness is cured, acclimatization supervenes. Some men never get acclimatized. They develop Chronic Mountain Sickness and die. A form of survival is migration to the low lands. The environment assailment-climatic aggresion,-may be defined as the noxious action of the Andean climate ("temple", from the Greek, meaning "dwelling-place") upon the dwellers from low lands and that of the sea coast upon the mountain men. The physiografic forces act upon the individual and the race in such a definite way that the behavior of high plateau societies has been confronted by its perennial influence. Thus it is not surprising that it can be traced in the historic documents and books about Tahuantisuyo and the Colonial Spanish Epoch. It has been proved that these facts were contemplated in the Inca's social legislation and that Pachacutec and other kings tood advantage of their knowledge in their war tactics (Garcilaso de la Vega). Climatic aggresion can be traced also in human and animal reproduction. The "San Nicolas de Tolentino miracle" concerning the first offspring born from Spanish ascendance fifty years after the Spaniards arrived at Potosi (12000 feet altitude), finds that the biological explanation is through a slow process of progressive race acclimatization of the human specie. The act of foundation of Lima (Lima, the capital of Perú, was foundation in 1535 and is 500 feet above sea level). points out that the capital was transferredfrom Jauja (10,500 feet altitude) to sea level because the pigs, horses and fowl did not reproduce. The observations of Father Cobo (XVII century) concerning the descendants (by crossing Spanish and Indian blood) might be considered as Mendelian anticipations. As a result of the balanced interdependence of man and milieu, acclimatization of Andean natives and foreign people may he considered as a rule by the fixation of men and animals on the Andes from a prehistoric time.Training for athletes implies the compensation of an oxygen debt produced by progressive exercise above normal requirements. Therefore the permanent altitude oxygen deficit, conversaly, must condition a compulsory stimulus to create athletics. Thus, to get accustomed to exercise is the altitude law of the body. Now, all the investigators agree on the extraordinary strength of the Andean men, and Colonial writers stress the fact that physical culture was incorporated in their daily life: in locating their cities and houses on trop of the countains; in their social organization, foot messengers (Chasquis) and Inca stretcher carriers; in the different cult expressions (apachetas ), in the selection of the nobility class (Huaracu's festivity and the "orejones", big ear rings ordeal) and finally in the wedding ceremonials (Acataimita and Paltay festivals). In these cases the training was carried out as for Olympic games, according to the strictest rules: camp concentration, adequate food, psychological tests, physical culture, abstinence and hygienic life in order to be fitted for the games. To the winners belonged the rights and honors. A bio-climatic determinism was actually impressed in the building of their societies so deeply saturated with the telluric environment. That is the answer to the sense of human migrations to lands of the same climate and the return nomadism which constitute the mitimaes organization, some kind of internal colonization built up on a cIimatic foundation. As a consequence, the continuous changes of population brought a perennial crossing of men from different lands but always keeping this transfer at a similar altitude and the same land. Thus the Inca's sociology was bio-cIimatic. The biological influence of the altitude was noticed in the individual, the race and the societies of America in peace, war and in colonization. The Spanish crown knew this fact and tried to promote it with adequate legislation that unfortunately remained only written. The Republic ignores this problem. During the emancipation wars whenever the Argentine troops fought in low lands as it happened in the proximity of Jujuy (1236 meters above sea level}, Salta (1185 meters) and Tucuman (477 meters) they were the winners, while they were defeated by the Andean high altitude troops in the Alto Perú, above 3,000 meters of altitude (Sipe-sipe, Ahoyuma and Guaqui.). San Martin refused to cross the high plateaus, as if he had an intuition about the climatic agression which had defeated the men of the low, lands previously. All the writers agree on the outstanding feature of the contradictory behavior of men: in their place of origin they were prominent warriors or showed good fighting spirit, but they lost their skill when they were at a high altitude. From the industrial standpoint, the knowledge of inferlity brought about by high altitude, has allowed selection of animals suited for reproduction. This selection has greatly improved the farming industry at high plateaus. As we have emphasized, climatic aggression on the reproductive organs has been shown since the arrival of the Spaniards to the Andes. The wisdom of the Inca's sociological laws as it appears from a historic standpoint confirms the knowledge they had about the influence of the high plateaus climate upon the individual, the race and the andean american soeieties.